Can emojis mean "Earthquake"?. (November 2020) - Raccanello, Daniela; Hall, Rob; Burro, Roberto
Abstract: With the increase in digital communications systems and social media, there is a need for simple graphics-based ways to signal the occurrence of major disasters. We describe the development and initial usability testing of a sign to indicate that an earthquake has occurred. We involved 264 Italian adults, who completed an online survey to evaluate the evocativeness, simplicity, and universality of 16 emojis depicting earthquakes. Through a Self-Organising Map analysis we identified four similar response profiles to the evocativeness scale, differing in their mean strength. A non-metric Multidimensional Scaling suggested that evocativeness was higher for the emojis featuring a damaged building. Linear Mixed Models indicated that emojis with fabricated vs. natural structures were judged as more evocative, simpler, and more universal when characterized by danger from falling objects. In some cases, adding behavioral elements increased evocativeness. Practical implications for informing the development of a new emoji for earthquakes are discussed. Highlights: We designed and tested the efficacy of emojis to signal earthquakes. Emojis varied for natural/fabricated structures, danger from falling objects (DFO). Emojis with fabricated structures and DFO were more evocative, universal, simpler. Adding behavioral elements to the emojis increased evocativeness of earthquakes. The findings may assist in improving communication of risk linked to earthquakes.